ANALISIS YURIDIS KETENTUAN PASAL 37 UNDANG-UNDANG DASAR 1945 SETELAH AMANDEMEN TENTANG PROSEDUR PERUBAHAN UNDANG-UNDANG DASAR DALAM PERSPEKTIF DEMOKRASI KONSTITUSIONAL - Putri Kemala Sari; Nila Trisna; Phoenna Ath Thariq (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
Indonesian independence is a new era in the formation of the constitution and order of state life. Because it was at this moment of independence that Indonesia first formed its written constitution in a standardized manner and compiled it into a state sheet. The constitution is called the 1945 Constitution of the Republic of Indonesia, which has been amended four times to date. The points that become the discussion are regarding the provisions contained in Article 37 regarding the procedure for amending the 1945 Constitution whether it has applied the principles of constitutional democracy because the last amendment of the amendment to the 1945 Constitution from the provisions of Article 37 cannot be implemented anymore. The purpose of this research is to examine and analyze whether the provisions of Article 37 of the 1945 Constitution have applied the principles of constitutional democracy. The research methodology used is normative juridical with a descriptive analysis approach. Based on the results of the research on the amendment procedure of the 1945 Constitution, it adopts a method of change known as "verfassungs-anderung", namely a way of changing the constitution deliberately in the manner specified in the constitution. Then use a system of changes "constitutional reform". With the "formal juridical" pathway and completed as changes by means of "formal amendments", namely changes to the constitution which are made in accordance with the provisions contained in the constitution. So in other words Article 37 of the 1945 Constitution regarding the procedures for amending the 1945 Constitution has inspired the values of democratic principles procedurally but the substance of the provisions of Article 37 of the 1945 Constitution is not fully applied to the principles of constitutional democracy because there are still many provisions in Article 37 regarding the procedures for amending the 1945 Constitution. This still needs to be studied in depth, because of its flexible nature after the changes, but its content is still rigid and difficult to change. Keywords : constitutional, democracy, , constitutional amendment procedure